Structure of the ceramide-bound SPOTS complex - Jan-Hannes Schäfer; Carolin Körner; Bianca M. Esch; Sergej Limar; Kristian Parey; Stefan Walter; Dovile Januliene; Arne Moeller; Florian Fröhlich (Nature Communications, 2023)
Abstract Sphingolipids are structural membrane components that also function in cellular stress responses. The serine palmitoyltransferase (SPT) catalyzes the rate-limiting step in sphingolipid biogenesis. Its activity is tightly regulated through multiple binding partners, including Tsc3, Orm proteins, ceramides, and the phosphatidylinositol-4-phosphate (PI4P) phosphatase Sac1. The structural organization and regulatory mechanisms of this complex are not yet understood. Here, we report the high-resolution cryo-EM structures of the yeast SPT in complex with Tsc3 and Orm1 (SPOT) as dimers and monomers and a monomeric complex further carrying Sac1 (SPOTS). In all complexes, the tight interaction of the downstream metabolite ceramide and Orm1 reveals the ceramide-dependent inhibition. Additionally, observation of ceramide and ergosterol binding suggests a co-regulation of sphingolipid biogenesis and sterol metabolism within the SPOTS complex.